Exploring the Influence of Age and Education Diversity on Employee Performance at Bhatbhateni Supermarket in Kathmandu Valley - Ghimire, Shiva Raj; Manandhar, Ujen; Ghimire, Sabina (Nepalese Journal of Business and Management Studies, 2023)
In today's diverse workplaces, understanding the relationship between workforce diversity and employee performance is crucial. Age diversity and education diversity are taken as independent variables, and employee performance is the dependent variable in this study. This study aims to examine the effects of these independent variables on the employee performance of Bhatbhateni Supermarket located at Thimi, Satdobato, Krishna Galli, and Koteshwor. Grounded in human capital theory, this study employs descriptive, relational, and causal research designs along with correlation and regression, which are used as major statistical tools considering the research objectives. The convenience sampling method was used in this study, where the survey utilized a self administered questionnaire as the data collection tool and collected responses from 146 employees. The findings concluded that there is a positive and significant relationship between age diversity and education diversity on employee performance. The study revealed that when there is a mix of ages and education levels in the workplace, employees tend to perform better. Therefore, this research highlights the important role of these two dimensions of workforce diversity in enhancing employee performance.